The Influence of Tourism Experience on Revisit Intention with Emotional Attachment as a Mediator (A Case Study at Kuta Beach) - PRIMANANDA, Pande Gde Bagus Naya; KUSUMA, A.A Made Indra Wijaya (Journal of Tourism Economics and Policy, 2025)
This study examines the role of tourism experience in shaping domestic tourists' revisit intentions in Bali in the post-pandemic context, sending visitors, and the issue of declining experience quality. Referring to the inconsistencies in previous findings, the study examined the influence of tourism experience on revisit intentions and the mediating role of emotional attachment. Data were collected through a survey of 140 respondents who visited in the past two years and analyzed using PLS-SEM. The measurement results showed valid and reliable indicators; The aesthetic and escapist dimensions were the most dominant, while the entertainment dimension was removed because it did not meet the criteria. Structurally, tourism experiences were shown to enhance emotional well-being, but not to increase revisit intentions. Emotional attachment also had no effect on revisit intentions and did not act as a mediator. The findings confirm that revisit decisions are more likely influenced by other factors, such as perceived value, satisfaction, accessibility, and attraction variety. Consequently, managers need to design strong experiences along with more direct retention strategies. Revisit incentive programs can be prioritized on an ongoing basis.